(untitled) (Bangladesh Journal of Botany, 2018)
Significant improvement in LAI, number of trifoliate, SPAD value of green leaf chlorophyll, dry matter accumulation, yield, harvest index (%) and nutrient content of mungbean were recorded due to application of 75% RDF + 2.5 t/ha vermicompost (VC) + Rhizobium (Rh)+ phosphorus solublizing bacteria (PSB), followed by 100% RDF + 2.5 t/ha VC and 100% RDF + Rh + PSB. The highest seed yield of mungbean was obtained with the application of 75% RDF + 2.5 t/ha VC + Rh + PSB (12.34 q /ha) followed by 100% RDF + 2.5 t/ha VC (12.05 q /ha) and 100% RDF + Rh+ PSB (11.95 q /ha).